Mechanical Performance of the Isolated and Perfused Heart of the Haemoglobinless Antarctic Icefish Chionodraco hamatus (Lonnberg): Effects of Loading Conditions and Temperature - B. TOTA; R. ACIERNO; AGNISOLA, CLAUDIO (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 1991)
Scaling of heart ventricle mass and body mass in the haemoglobinless Antarctic fish Chionodraco hamatus Lonnberg shows a relationship similar to those reported for other 'cardiomegalic' icefish (Chaenocephalus aceratus and Channichthys rhinoceratus). An in vitro preparation of the heart of C. hamatus was set up to investigate the mechanical performance of this heart at different preloads and afterloads. It appears that this heart is well adapted to working within a range of preloads varying from -0.07 to -0.04 kPa, while it is unable to sustain increases of afterloads higher than 3.0 kPa. As in other teleosts, heart rate is unaffected by changes in preload and afterload. Increase in temperature from 0.5 to 5.8-degrees-C affects heart rate whereas stroke volume is unaffected. On the whole, the in vitro data are similar to those in vivo measured in another icefish, C. aceratus and show that the heart of C. hamatus works as a typical volume pump. This is discussed in relation to both the structural constraints related to the cardiac design of this icefish and the biology of this unique vertebrate.